THE UNITY OF OPPOSITES OR THE ABSOLUTE MAXIMUM RUSSIAN PHILOSOPHY OF HISTORY - Anton Aleksandrovich Antipov (Science and Innovation Center Publishing House, 2017)
The modern foreign policy of modern Russia, and its discussion seem to be situational, profoundly contradictory and illogical. The study of Russian philosophy of history allows us to understand the content of contemporary political discourse, and to see the foundation of the current foreign policy context that is formed around the Russian state.